If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 = x Reorder the terms: 14 + 2x = x Solving 14 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 14 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 14 + 1x = x + -1x Combine like terms: x + -1x = 0 14 + 1x = 0 Add '-14' to each side of the equation. 14 + -14 + 1x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 1x = 0 + -14 1x = 0 + -14 Combine like terms: 0 + -14 = -14 1x = -14 Divide each side by '1'. x = -14 Simplifying x = -14
| a-584=-22a-9 | | 8x-7=7x+12 | | 7(t-4)+5t=6(2t+3)-9 | | -10y+18=-31(54-7)-8 | | a-589=-22a-9 | | X-17+(-5)=-23 | | 14x=30+20x | | ln(3x+5)=4 | | t-54=2-9 | | 4x^2+4x=-36 | | 3x=21+12 | | 2x-5=34 | | 8x=600 | | 2x=5y-10 | | 2-11=12-d | | 5x+3(x-5)=6x+2x-15 | | 5x+160=70 | | 600x=8 | | 4.5=10x | | 5a+4(3am-8)=4+13a | | 5x+33=123 | | -7(-1x+9)=-126 | | -4x-46=18 | | 17z+10=39 | | n-335=21n-5 | | x^5-49x^3=0 | | 2h+1=6 | | 5+y=6(5+0.1) | | 25d+0.45m=40d+0.25m | | 10x^3-8x^2-18x= | | -9-2x=-41 | | 15b+24c+33= |